UNEMPLOYMENT CHALLENGE IN NIGERIA: VOCATIONAL EDUCATION THROUGH OPEN & DISTANCE LEARNING MODEL TO THE RESCUE - Ojewumi, A K; Olasupo, M O (Sokoto Educational Review, 2017)
The paper reviewed the present status of unemployment situation in Nigeria with emphasis on university graduates. Effort was also made to examine the role vocational education through Open Distance Learning (ODL) can play to address this national problem. Included is recommendation of a vocational training programme developed for graduates seeking employment in areas as Fashion, Interior Decoration, Leather works, Accessories etc. The importance of this ODL based model of vocational education and training programme has great importance and relevance in countries where unemployment is a serious challenge and where there is a great need of providing training to multitude of unemployed youths at different levels to enable them have skills that will afford them the opportunity to contribute their quota to the economic advancement of their country.